2023
DOI: 10.1038/s41589-023-01374-7
|View full text |Cite
|
Sign up to set email alerts
|

Engineering cellular communication between light-activated synthetic cells and bacteria

Abstract: Gene-expressing compartments assembled from simple, modular parts, are a versatile platform for creating minimal synthetic cells with life-like functions. By incorporating gene regulatory motifs into their encapsulated DNA templates, in situ gene expression and, thereby, synthetic cell function can be controlled according to specific stimuli. In this work, cell-free protein synthesis within synthetic cells was controlled using light by encoding genes of interest on light-activated DNA templates. Light-activate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…We believe these controllable plasmids might be especially relevant for studies in developmental biology 26,27 and population dynamics. 60…”
Section: Discussionmentioning
confidence: 99%
“…We believe these controllable plasmids might be especially relevant for studies in developmental biology 26,27 and population dynamics. 60…”
Section: Discussionmentioning
confidence: 99%
“…Quorum sensing, which is the communication behavior of cells to detect and respond to cell population density, has been extended to molecular robots and bacterial populations. 327–329 Remarkably, Smith et al reported light-activated GUVs that could perform quorum-sensing-based communication with bacteria 329 (Fig. 13(c)).…”
Section: Applications Of Molecular Robotsmentioning
confidence: 99%
“…Communication can also be engineered using a synthetic biology approach, based on the expression of proteins inside vesicles by means of transcription-translation (TXTL) reactions. , In these reactions, protein synthesis machinery is encapsulated together with the DNA sequences encoding the proteins of interest. Upon rational design of the plasmid, protein expression can be activated in the presence of certain species (such as membrane-permeable quorum sensing molecules) or upon application of light . Then, the in situ expressed proteins can either form pores on the membrane to induce the release of entrapped cargo or catalyze certain reactions to produce chemical messengers. , …”
Section: Tools To Engineer Chemical Communicationmentioning
confidence: 99%
“…In more recent work, Mansy’s group established communication between GUV-based artificial cells and eukaryotic cells (kidney or neural) via the release of brain-derived neurotrophic factor (BDNF) upon addition of external 3O6CHSL, producing protein expression or neural differentiation as a result . Other groups have employed TXTL machinery for constitutive (without external input addition) or light-controlled expression of different enzymes in GUVs, which subsequently catalyze the production of membrane-permeable gene inducers as chemical messengers to communicate with bacteria (that trigger the expression of fluorescent proteins as a response) …”
Section: Models Of Chemical Communicationmentioning
confidence: 99%